PROSES PEMBERDAYAAN MASYARAKAT BERBASIS RUKUN WARGA (PMB RW) DI KOTA PEKANBARU - Talgia . (Jurnal Renaissance, 2017)
The purpose of this research is to analyze the process of Community Empowerment Based on Rukun Warga and maximum on the basis of rill. By using qualitative method by obtaining data from informen accurately and analyzing problems arising from the community empowerment process based on the pillars of the residents in the three urban villages: Simpang Tiga, Tangkerang Labuai and Tangkerang Selatan Sub-districts Bukit Raya Sub-district, Pekanbaru City. Furthermore, community-based empowerment process of harmonious citizens can be concluded to run optimally. The model of community empowerment process based on community-based in this research, which is : enable, empower and protect.Key words: Policy, Empowerment and Community Participation